RITUAL, EMBODIMENT AND MEANING-MAKING IN TRAUMA RECOVERY. - Ow, Gary (African Journal of Social Sciences & Humanities Research, 2026)
Trauma recovery frequently falters when therapeutic intervention relies primarily on verbal insight and cognitive reframing. While such approaches can improve understanding, they often fail to engage the embodied and symbolic dimensions through which traumatic experience is originally encoded. This paper advances a model of trauma recovery grounded in ritualized embodiment and meaningmaking, proposing that durable change emerges when bodily sensation, symbolic action and narrative authorship are integrated within a structured therapeutic container. This conceptual and interdisciplinary theoretical paper develops a mechanism model of trauma recovery grounded in ritualized embodiment and meaning-making. Drawing on literature from trauma studies, depth psychology, anthropology, and narrative identity research, it argues that ritual functions as a transitional technology: translating diffuse affect and pre-verbal experience into symbolic form without requiring immediate verbalization. Embodied ritual practices—such as posture, gesture, spatial orientation, and controlled enactment—stabilize affect, regulate arousal, and create conditions under which new meanings can be generated safely. Meaning-making is reframed not as retrospective interpretation but as active authorship, in which individuals renegotiate their relationship to memory, identity, and agency. The paper proposes a phased framework for trauma recovery that moves from somatic stabilization to symbolic engagement to narrative integration. Within this framework, ritual operates as a mediating structure that protects against both emotional overwhelm and premature cognitive closure. The model emphasizes containment, timing and client sovereignty, challenging assumptions that continuous emotional processing is necessary for therapeutic progress. Instead, recovery is conceptualized as the gradual restoration of the capacity to choose how experience is held, interpreted and lived. By articulating the mechanisms through which ritualized embodiment supports meaning-making, this paper contributes a theoretically coherent and clinically applicable account of trauma recovery that bridges somatic, symbolic and narrative approaches.